(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Eudora Welty’s short story “The Death of a Traveling Salesman” (1936) is a poignant exploration of isolation, existential despair, and the human longing for connection. Set in the American South during the interwar period, the story follows R. J. Bowman, a sick and emotionally fatigued salesman, whose journey into an unfamiliar rural landscape leads to profound personal revelations. Through symbolic imagery, psychological introspection, and minimalist narrative style, Welty constructs a narrative that challenges modern ideals of progress and material success. This analysis examines how Welty uses setting, symbolism, and character psychology to convey the story’s central themes of alienation and spiritual awakening.